Melatonin Receptor 1A (MTNR1A) Gene Polymorphism in Cross-Bred Hamdani Sheep: A Preliminary Study - TURGUT, Ali Osman; KOCA, Davut (ISPEC Tarım Bilimleri Dergisi, 2024)
Melatonin plays a key role in regulating several vital physiological processes, including the maturation and functioning of the reproductive system, pubertal development, seasonal reproduction, and adaptation. The activation of the melatonin hormone is facilitated by melatonin receptors. This study aimed to investigate melatonin receptor 1A (MTNR1A) gene polymorphism in cross-bred Hamdani sheep. A total of 102 cross-bred Hamdani ewes were used as animal material. DNA was extracted from whole blood. The 824 bp PCR products from the exon II region of the MTNR1A gene underwent analysis for restriction fragment length polymorphism (RFLP) using the RsaI restriction enzyme. In the study, RR, Rr, and rr genotypes were detected for MTNR1A gene in cross-bred Hamdani sheep. Genotype frequencies for RR, Rr, rr were 0.69, 0.27, and 0.04, respectively. Allele frequencies were detected as 0.82 and 0.18 for R and r alleles, respectively. In conclusion, more comprehensive research investigating association between MTNR1A genotypes and reproductive traits should be carried out in cross-bred Hamdani sheep.